RNA Editing and Its Roles in Plant Organelles - Hao, Wei; Liu, Guoxiang; Wang, Weipeng; Shen, Wei; Zhao, Yuping; Sun, Jialiang; Yang, Qiuyue; Zhang, Yaxin; Fan, Wenjia; Pei, Shuaishuai; Chen, Zhuanqing; Xu, Dongbei; et al. (Frontiers in Genetics, 2021)
RNA editing, a vital supplement to the central dogma, yields genetic information on RNA products that are different from DNA templates. The conversion of C-to-U in mitochondria and plastids is the main kind of RNA editing in plants. Various factors have been demonstrated to be involved in RNA editing. In this minireview, we summarized the factors and mechanism involved in RNA editing in plant organelles. Recently, the rapid development of deep sequencing has revealed many RNA editing events in plant organelles. We further reviewed RNA editing events identified in plant organelles through deep sequencing data. Numerous studies have shown that RNA editing plays essential roles in diverse processes, such as the biogenesis of chloroplasts and mitochondria, seed development, and stress and hormone responses. Finally, we discussed the functions of RNA editing in plant organelles.